Amino acid motifs in natural products: synthesis of O-acylated derivatives of (2S,3S)-3-hydroxyleucine - Ries, Oliver; Büschleb, Martin; Granitzka, Markus; Stalke, Dietmar; Ducho, Christian (Beilstein Journal of Organic Chemistry, 2014)
(2S,3S)-3-Hydroxyleucine can be found in an increasing number of bioactive natural products. Within the context of our work regarding the total synthesis of muraymycin nucleoside antibiotics, we have developed a synthetic approach towards (2S,3S)-3-hydroxyleucine building blocks. Application of different protecting group patterns led to building blocks suitable for C- or N-terminal derivatization as well as for solid-phase peptide synthesis. With respect to according motifs occurring in natural products, we have converted these building blocks into 3-O-acylated structures. Utilizing an esterification and cross-metathesis protocol, (2S,3S)-3-hydroxyleucine derivatives were synthesized, thus opening up an excellent approach for the synthesis of bioactive natural products and derivatives thereof for structure activity relationship (SAR) studies.
Keywords: chiral pool; cross metathesis; esterification; β-hydroxy-α-amino acids; natural products